2018
DOI: 10.1016/j.numecd.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Lower C-reactive protein and IL-6 associated with vegetarian diets are mediated by BMI

Abstract: The lower CRP and IL-6 concentrations among vegetarians may be mediated by BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 47 publications
0
23
1
2
Order By: Relevance
“…There is also some indication that food legumes may reveal the anti-inflammatory action that is attributed to lectins and peptides [ 45 ]. In general, observational studies show that adherence to plant-based diets is associated with lower levels of inflammation markers, e.g., C-reactive protein, fibrinogen, and interleukin-6, compared to omnivorous diets [ 46 , 47 , 48 ]. This is further supported by interventional trials showing that plant-based dietary approaches are associated with lower scores of Dietary Inflammatory Index and improved inflammatory markers in subjects with high BMI [ 49 , 50 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is also some indication that food legumes may reveal the anti-inflammatory action that is attributed to lectins and peptides [ 45 ]. In general, observational studies show that adherence to plant-based diets is associated with lower levels of inflammation markers, e.g., C-reactive protein, fibrinogen, and interleukin-6, compared to omnivorous diets [ 46 , 47 , 48 ]. This is further supported by interventional trials showing that plant-based dietary approaches are associated with lower scores of Dietary Inflammatory Index and improved inflammatory markers in subjects with high BMI [ 49 , 50 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a meta-analysis that examined the relationship between consumption of a vegetarian diet and inflammation, a minimum duration of two years of following a vegetarian diet was needed to see lower CRP levels [57]. Other studies also have suggested that low levels of inflammation among vegetarians are mediated by BMI [58] or gut microbiota composition [59]. While most IMAGINE participants were overweight or obese, not all participants had a BMI above 25 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Las dietas vegetarianas han sido reconocidas desde hace mucho tiempo por conferir protección contra enfermedades como las cardiovasculares, 7 inflamatorias, la diabetes mellitus tipo 2 8,9 y el cáncer 10 y contra factores de riesgo cardiometabólicos como la hipertensión arterial 11 y la obesidad, 12,13 pero el papel de la dieta vegetariana en la fertilidad masculina ha sido poco estudiado y la información aun es controversial.…”
Section: Introductionunclassified